METHODS OF FORMING COMPETENCIES IN APPLICANTS FOR THE SPECIALTY «CYBERSECURITY» WHEN PERFORMING A COURSE ASSIGNMENT IN THE DISCIPLINE «MATHEMATICAL FOUNDATION OF INFORMATION SECURITY» - Pakhomova, Victoria (SWorld-Ger Conference proceedings, 2024)
The methodology of "ComparSystem_MathFIS" for the formation of professional and subject competencies of applicants for the degree "Bachelor" in the specialty "Cybersecurity" at fulfillment of the course task in the discipline "Mathematical Foundations of